Transport of energy by ultraintense laser-generated electrons in nail-wire targets - Ma, T; Key, M; Mason, R; Akli, K; Daskalova, R; Freeman, R; Green, J; Highbarger, K; Jaanimagi, P; King, J; Lancaster, K; Hatchett, S; et al. (2009)
Nail-wire targets (20 μm diameter copper wires with 80 μm hemispherical head) were used to investigate energy transport by relativistic fast electrons generated in intense laser-plasma interactions. The targets were irradiated using the 300 J, 1 ps, and 2 × 1020 W · cm-2 Vulcan laser at the Rutherford Appleton Laboratory. A spherically bent crystal imager, a highly ordered pyrolytic graphite spectrometer, and single photon counting charge-coupled device gave absolute Cu Kα measurements. Results show a concentration of energy deposition in the head and an approximately exponential fall-off along the wire with about 60 μm 1/e decay length due to resistive inhibition. The coupling efficiency to the wire was 3.3 ± 1.7% with an average hot electron temperature of 620 ± 125 keV. Extreme ultraviolet images (68 and 256 eV) indicate additional heating of a thin surface layer of the wire. Modeling using the hybrid E-PLAS code has been compared with the experimental data, showing evidence of resistive heating, magnetic trapping, and surface transport. © 2009 American Institute of Physics.